Parental Age and Gender: How they Influence Knowledge and Perceptions of Inclusive Education for Children with Intellectual Disability - Jacob, Udeme Samuel; Pillay, Jace (Journal of Intellectual Disability - Diagnosis and Treatment, 2025)
Background: This study investigated how parental age and gender influence their knowledge and perspectives of inclusive education for their children with intellectual disabilities (ID). This study is essential as it provides valuable insights into how parental factors, such as age and gender, can shape their knowledge, perceptions, and attitudes toward inclusive education, which will likely impact the educational experiences and outcomes for children with intellectual disabilities. Methods: Employing a cross-sectional research design, the study surveyed 96 parents, consisting of 55 males (57.3%) and 41 females (42.7%). The participants were categorised by age: under 25 (n=20, 20.8%), 25-34 (n=24, 25.0%), 35-44 (n=28, 29.2%), and 45 and above (n=24, 25.0%). Data were collected using a structured questionnaire, demonstrating a reliability coefficient of 0.88 (Cronbach's alpha). The data analysis used Multivariate Analysis of Variance (MANOVA) to assess the main and interaction effects of parental age and gender on their knowledge regarding inclusive education. Results: Tests of Between-Subject Effects indicated a significant interaction between age and gender, F (3, 88) = 5.67, p < 0.01, revealing that older female parents (M = 4.10) had higher knowledge scores than older male parents (M = 3.60). Estimated marginal means supported these findings, explicitly showing significant differences between parents aged 25-34 and 45 and above (p < 0.05). These differences are evident in pairwise comparisons, particularly in the 35–44-year-old age cohort (M = 3.95). Conclusion: The results indicate that age and gender influence parental knowledge and perceptions of inclusive education. A targeted intervention considering these factors is crucial to enhancing supportive educational environments for children with ID.